PENGGUNAAN MEDIA RODA BERPUTAR UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS V SDN 31 CAKRANEGARA - Syukron Zul Ramdan (Al-mujahidah, 2024)
This study aims to determine the effectiveness of the use of rotating wheel media in encouraging the learning interest of grade V students of SDN 31 Cakranegara. Problems in the learning process can occur, one of which is that the media used is not appropriate. This study uses a qualitative approach with a descriptive method and the collection of data use techniques using field research and library research. The results of the experiment of spinning wheel media in grade V of SDN 31 Cakranegara showed that students showed interest in learning when using spinning wheel media, this was shown by the enthusiastic attitude of students during the learning process.